Pola Komunikasi Organisasi Dinas Komunikasi dan Informatika Kabupaten Tanah Datar dalam Mengelola Youtube Channel Tanah Datar TV - Daniel, Deno Aulia; Ismi Wahidar, Tutut (Lenvari: Journal of Social Science, 2023)
An organizational communication pattern is a relationship between two or more people in the process of sending and receiving the right way so that the intended message can be understood. The fact that occurs in the Communication and Informatics Service is that differences in the quality of human resources such as less responsiveness and less effective communication flows result in differences in perception between leaders and employees, therefore organizational communication patterns are needed to coordinate management in order to produce a good communication process so that the goals of the Communication and Information Department can be achieved. The aim of this research is to determine the communication patterns used, and the supporting and inhibiting factors in the communication process that occurs at the Tanah Datar Regency Communication and Information Service. This research uses qualitative research methods. The subjects of this research were the Head of the Communication and Information Service, the Head of Public Communication Information, and the Tanah Datar Tv YouTube Channel Team who were selected using a purposive technique. Data collection techniques consist of observation, interviews and documentation. Whereas. The results of this research show that organizational communication patterns in improving service quality at Diskominfo use the Wheel pattern, Y pattern and pattern.